Obtaining Patient Priorities in a Multiple Sclerosis Comprehensive Care Center: Beyond Patient-Reported Outcomes. (August 2020) - Miller, Deborah M; Moss, Brandon; Rose, Susannah; Li, Hong; Schindler, David; Weber, Malory; Planchon, Sarah M; Alberts, Jay; Boissy, Adrienne; Bermel, Robert
Background: In order to provide patient center care, our multiple sclerosis (MS) clinic assesses patient concerns before clinical encounters, first by asking the optional qualitative question "What is the most important thing you what your health-care provider to know today" (most important concern of the patient [MIPC]) and then completing quantitative patient-reported outcome measures (PROMs) including Quality of Life in Neurological Disorders (Neuro-QoL). Both sets of questions are designed to facilitate encounters that address patients' values and preferences. Objective: Determine whether the qualitative MIPC responses provided unique information not included in PROMs or clinical assessments. Methods: We randomly selected 400 first-time MIPC responders and 400 first-time MIPC nonresponders from 2788 participants in our database. We categorized MIPC responses by content and number of unique concerns and appended them to the Neuro-QoL framework. Nonresponders were compared to those who provided 1 and 2 or more responses. Results: Several MIPCs MS symptoms categories were added to the Neuro-QoL Physical domain. Most important concern of the patients work and cost-of-care categories were added to the Social Domain. Domains regarding treatment satisfaction and disease management were added. Two hundred thirty (58%) MIPC respondents reported 1 concern, 140 (35%) expressed 2 to 6 concerns, and 30 (7%) reported MS-unrelated concerns and not analyzed. Physical symptoms were the most common MIPC (69.9%). Respondents with more concerns were more likely African American, lacked private insurance, and worse disability. Conclusions: Importantly, MIPC responders described idiosyncratic symptoms, disease management, and social concerns not included in the PROMS, suggesting the MIPC question offered patients a unique opportunity to share specific concerns with their providers.